The sea of lost girls [large type] - Goodman, Carol (Wheeler Publishing, a part of Gale, a Cengage Company, 2020)
"Tess has worked hard to keep her past buried, where it belongs. Now she's the wife to a respected professor at an elite boarding school, where she also teaches. Her seventeen-year-old son, Rudy, whose dark moods and complicated behavior she's long worried about, seems to be thriving: he has a lead role in the school play and a smart and ambitious girlfriend. Tess tries not to think about the mistakes she made eighteen years ago, and mostly, she succeeds. And then early one morning she gets a text at 2:50 AM: it's Rudy, asking for help. When Tess picks him up she finds him drenched and shivering, with a dark stain on his sweatshirt. Four hours later, Tess gets a phone call from the Haywood school headmistress: Lila Zeller, Rudy's girlfriend, has been found dead on the beach, not far from where Tess found Rudy just hours before. As the investigation into Lila's death escalates, Tess finds her family attacked on all sides. What first seemed like a tragic accidental death is turning into something far more sinister, and not only is Tess's son a suspect but her husband is a person of interest too. But Lila's death isn't the first blemish on Haywood's record, and the more Tess learns about Haywood's fabled history, the more she realizes that not all skeletons will stay safely locked in the closet"--Page [4] of cover.